Exploration and characteristic of the local cassava accessions from Central Sulawesi - Amin, Mirawanty; Syafruddin, Syafruddin; Saidah, Saidah; Suwitra, I Ketut; Negara, Abdi; Ardjanhar, Asni; Asnawi, Asnawi (Jurnal Ilmu Pertanian, 2024)
Cassava serves as a local food that contributes to food variety, enhancing food security and family nutrition. This is feasible due to Indonesia's extensive biodiversity, which facilitates the availability of varied and high-quality food. Each location has cassava with distinct properties. This research aimed to identify the presence of native cassava and their specific properties in Central Sulawesi. The used methodology included a survey and observation of plant agronomic and morphological characteristics, according to the General Guide for the Preparation of Food Crop Variety Descriptions established by the Centre for Plant Protection and Agricultural Licensing of the Ministry of Agriculture of the Republic of Indonesia. The investigation discovered three indigenous cassava accessions in Palolo District, Sigi Regency, Central Sulawesi: Kahubi Bula, Kahubi Palolo 1, and Kahubi Palolo 2. The three accessions possess distinct morphological, agronomic, and nutritional properties. Kahubi Bula has a greater stem diameter, whereas Kahubi Palolo 2 exhibits the lowest tuber size. The cyanide levels in the three accessions exhibited the traits of cassava, characterized by a sweet flavour owing to their low concentrations: 0.07 for Kahubi Bula, 0.01 for Kahubi Palolo 1, and 0.08 for Kahubi Palolo 2.